Bortezomib-releasing silica-collagen xerogels for local treatment of osteolytic bone- and minimal residual disease in multiple myeloma - Hose, Dirk; Ray, Seemun; Rößler, Sina; Thormann, Ulrich; Schnettler, Reinhard; De Veirman, Kim; Khassawna, Thaqif el-; Heiss, Christian; Hild, Anne; Zahner, Daniel; Alagboso, Francisca; Henss, Anja; et al. (Journal of hematology & oncology, 2024)
Accumulation of malignant plasma cells in the bone marrow causes lytic bone lesions in 80% of multiple myeloma patients. Frequently fracturing, they are challenging to treat surgically. Myeloma cells surviving treatment in the presumably protective environment of bone lesions impede their healing by continued impact on bone turnover and can explain regular progression of patients without detectable minimal residual disease (MRD). Locally applicable biomaterials could stabilize and foster healing of bone defects, simultaneously delivering anti-cancer compounds at systemically intolerable concentrations, overcoming drug resistance.
Gesehen am 20.03.2025